Inventory Management: Optimizing Inventory in The Shoe Business at Sneakers One, Bandung - Ester Manik; Iwan Sidharta; Kadir Kadir; Boy Suzanto; Nenny Rinawati; Retno Resawati; Abia Karen Meilita; Devi Desiyanti; Shilfa Irziani Kamal; Tri Puji Citasari (LPPM STMIK Mardira Indonesia, 2026)
This community service activity aims to enhance inventory management at the shoe business Sneakers One in Bandung. The main issue faced is the complexity of inventory management, which arises from variations in sizes, models, and rapid changes in trends. Through qualitative methods and field research involving lecturers and students, we provide recommendations to utilize sales data and appropriate inventory management methods.The results indicate that the implemented inventory system is quite effective, prioritizing fast-moving products and ordering new items in small quantities. Although the company has adopted a simple Economic Order Quantity (EOQ) concept, it has yet to implement a formal calculation system. We recommend conducting a more in-depth inventory management analysis, focusing on demand-based stock management, inventory efficiency, and risk reduction.